(In)congruities between Political Messages and Popular Music: An Analysis of Campaign Songs in U.S. Presidential Elections. Issue 4 (4th July 2021) - Johnson, Lottie Elizabeth; Haden Church, Scott; Randle, Quint
ABSTRACT: This study presents a rhetorical analysis of the popular songs selected by the major party candidates for their campaigns during the U.S. presidential elections from 1972–2016. Our analysis reveals that music is a form of political expression that, depending on the way it is incorporated, can either bolster or hinder a candidate's platform. Both Republican and Democratic presidential candidates have largely made use of congruity in their campaign songs, with that congruity only increasing over time. In particular, findings indicated that musically incongruent songs that are politically reinforcing could be a significant boost for candidates striving to expand their base. The research also indicated that Republican candidates tend to select songs that are positive and patriotic in nature, while their Democratic counterparts incorporate songs that offer a critique of the nation.